Resistance of a mixed bacterial culture isolated from bee dysbiosis to disinfectant in laboratory conditions - A. R. Lakhman; T. O. Romanishina; M. V. Zastulka; V. L. Behas; O. Ye. Galatiuk (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки)
Disinfection is one of the components of preventive actions to prevent disease in animals by infectious agents. Through the elimination of agents of infectious diseases in the environment, it is able to interrupt the mechanisms of the epizootic process. For the development of beekeeping and obtaining quality and products, it is necessary to carry out activities in apiaries, which include disinfection. The introduction of new disinfectants in the field is possible after preliminary laboratory tests. The aim of our research objective to investigate the resistance of a mixed bacterial culture isolated from bees with the symptoms of dysbiosis to disinfectant under laboratory conditions. Bacteriological investigations carried out in Petri dishes using meat-peptone agar and Mueller-Hinton agar.  The disinfectant diluted with distilled water at concentrations of 0.25 %, 0.5 %, 1,25 % and 2,5 %. On the Mueller Hinton agar, the bacterial elimination zones recorded at 1.25 % (11,6 ± 0,45 mm) and 2.5 % (12,4 ± 0,27 mm) concentration of disinfectant at 1 day of investigation, and 7,4 ± 0,27 mm (1,25 %), 11,2 ± 0,42 mm (2.5 %) at 72 hours of the experiment, respectively. In addition, the bacterial growth inhibition effect increased with experimental time and ranged from 24.0 ± 0.35 mm (0.5 %) to 28.2 ± 0.22 mm (2.5 %) on day 3 of the study. Bacteriostatic and bactericidal effects appeared to be less pronounced on meat-peptone agar. The highest diameters of inhibition of the processes of reproduction and development of microorganisms from mixed microbial association on this medium were recorded at 1.25 % and 2.5 % concentrations of the disinfectant at the 3rd day of the investigation with diameters of the zones of inhibition of growth 15.6 ± 0.45 mm and 26.4 ± 0.27 mm, respectively. The specificity of diffusion of the investigated active substance from the discs into the agar medium thickness was also noted. This effect has a varying effect on infectious agents in in vitro experiments. Thus bacteriological laboratory experiments should be performed on several culture media in purpose of obtaining accurate results. The analysis of the obtained results indicates the demonstration of antimicrobial effect of the investigated disinfectant against mixed bacterial culture in the form of bactericidal and bacteriostatic actions. Therefore, a promising direction of research for veterinary doctors and apiary business owners is the search for effective and efficient disinfectants. Laboratory investigation of the activity of a remedy are the first step before it is approbation.